Ambulatory Hysteroscopy in Abnormal Uterine Bleeding: A Tertiary Care Hospital Perspective - Nabila Iram; Bushra Zahid Saeed; Shagufta Parveen (Shalamar Medical & Dental College, Lahore, Pakistan, 2022)
Background: To avoid delays in outpatient facilities for managing benign gynecological conditions like abnormal uterine bleeding (AUB), there is a need to evaluate the usage of unconventional methods like outpatient hysteroscopy. Objectives: To evaluate the usage of outpatient diagnostic hysteroscopy in women with abnormal uterine bleeding. Methods: An observational study was conducted at the Obstetrics and Gynecology Department of Combined Military Hospital, Kharian. The study included 56 women having AUB with or without a history of failed medical treatment. The study participants underwent outpatient diagnostic hysteroscopy. Diagnostic hysteroscopy was done under the local para-cervical block in the Outpatient department. Procedure indications, outcome and biopsy findings were recorded on predesigned proformas. Results: Median age of the study participants was 44 years. The most common indications for diagnostic hysteroscopy were postmenopausal bleeding (34%) and heavy menstrual bleeding (28%). Hysteroscopy outcomes included endometrial biopsy (34%), discharge with no biopsy (25%), further test and evaluations required (21%), and admission due to failed outpatient procedures (20%). Sixty-two percent of the study participants had normal biopsy findings while other biopsy findings included polyps (20%), fibroids (14%) and endometrial hyperplasia (4%). Nine percent had unsuccessful hysteroscopy due to patient refusal to proceed. Conclusion: Outpatient hysteroscopy can be helpful in the early and rapid diagnosis of women with abnormal uterine bleeding.